2020
DOI: 10.3390/antiox9121187
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin/Nrf2/NLRP3 Connection in Mouse Heart Mitochondria during Aging

Abstract: Aging is a major risk for cardiovascular diseases (CVD). Age-related disorders include oxidative stress, mitochondria dysfunction, and exacerbation of the NF-κB/NLRP3 innate immune response pathways. Some of the molecular mechanisms underlying these processes, however, remain unclear. This study tested the hypothesis that NLRP3 inflammasome plays a role in cardiac aging and melatonin is able to counteract its effects. With the aim of investigating the impact of NLRP3 inflammasome and the actions and target of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 147 publications
6
46
0
Order By: Relevance
“…Recent studies determined that oral melatonin supplementation preserves normal structure and muscular activity in aged mice. These studies also confirmed the NLRP3 inflammasome implication in muscular aging [ 26 , 29 ]. Although there are some miRs involved in the regulation of the inflamma-pathways and of the NLRP3 inflammasome activity, it is not known whether their expression changes in aged muscle and what effect melatonin can exert on their expression with age.…”
Section: Introductionsupporting
confidence: 62%
See 1 more Smart Citation
“…Recent studies determined that oral melatonin supplementation preserves normal structure and muscular activity in aged mice. These studies also confirmed the NLRP3 inflammasome implication in muscular aging [ 26 , 29 ]. Although there are some miRs involved in the regulation of the inflamma-pathways and of the NLRP3 inflammasome activity, it is not known whether their expression changes in aged muscle and what effect melatonin can exert on their expression with age.…”
Section: Introductionsupporting
confidence: 62%
“…Melatonin (N-acetyl-5-methoxytryptamine, aMT) is a hormone involved in multiple functions, including antioxidative, anti-inflammatory, and immunomodulatory, and mitochondrial protective effects [ 23 , 24 , 25 , 26 ]. It is originally isolated from the pineal gland and is considered as a regulator of circadian rhythms and seasonal breeding [ 27 ]; however, it is currently known that melatonin is widely produced and distributed in all tissues and organs, including the skeletal muscle [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of action of LLLT is based on photon energy absorption by cytochrome oxidase, the terminal enzyme in the mitochondrial respiratory chain. LLLT can provide neuroprotection and cognitive enhancement by facilitating mitochondrial respiration, with hormetic dose-response effects and brain region activational specificity [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…This evidence supports the crucial role of endogenous melatonin in cardiovascular pathologies [ 194 ]. Melatonin can have an antiapoptotic effect associated with restoring Nrf2 antioxidant capacity (one of the main molecules responsible for detecting oxidative stress damage), improving this way mitochondria ultrastructure altered by aging [ 195 ]. Additionally, cardioprotection by melatonin against oxidative stress and arrhythmias could be widely explained by modulation of ion channels, AP and Cx43 expression [ 196 198 ].…”
Section: Melatonin As a Potential Antiarrhythmic Treatment In Aginmentioning
confidence: 99%